Development of the JARE deep ice coring system - Yoshiyuki Fujii; Hideaki Motoyama; Hideki Narita; Kunio Shinbori; Nobuhiko Azuma; Yoiti Tanaka; Moriatsu Miyahara; Akiyoshi Takahashi; Okitsugu Watanabe (National Institute of Polar Research, 1990)
A deep ice coring system, which is to be used a top the Queen Maud Land ice sheet in 1994-1995 with a plan named "Dome Project", has been developed since 1988. A mechanical system was adopted because of its less power consumption and smaller size compared with a thermal system. Experiments were done for mechanisms of ice cutting, chip transportation, chip storage, antitorque, monitoring sensors, and winch control with a 20-m drill experiment tower. Experiments were also done in Antarctica. This is an interim report of the development of the JARE deep ice coring system.